2020
DOI: 10.3989/ris.2020.78.1.18.096
|View full text |Cite
|
Sign up to set email alerts
|

Bullying y maquiavelismo en la universidad a través del análisis de redes sociales

Abstract: Los objetivos de este estudio son detectar combinaciones de acciones maquiavélicas y de bullying (acoso escolar) y señalar sus determinantes. Se ha recopilado una muestra de cinco redes de estudiantes de los departamentos de Educación Superior en el centro de Grecia (Administración de Empresas, Veterinaria y Educación Física & Ciencias del Deporte) (245 nodos). Se han utilizado cuestionarios estandarizados. Se ha implementado análisis de redes sociales, Spearman y PCA. El departamento de Educación Física e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
2
0
1
Order By: Relevance
“…Barbaranelli et al (2018) found amoral-Machiavellian students to be more likely to engage in academic dishonesty in situations where their peers practice it. Machiavellian students who attempt to gain information from their peers are more likely to hurt others (Spanou et al, 2020). On the other hand, in an earlier study by Nguyen and Pham (2015) who examined ethical attitudes of business students from Vietnam and the United States, the authors found high ethical attitudes towards business.…”
Section: Literature Reviewmentioning
confidence: 92%
“…Barbaranelli et al (2018) found amoral-Machiavellian students to be more likely to engage in academic dishonesty in situations where their peers practice it. Machiavellian students who attempt to gain information from their peers are more likely to hurt others (Spanou et al, 2020). On the other hand, in an earlier study by Nguyen and Pham (2015) who examined ethical attitudes of business students from Vietnam and the United States, the authors found high ethical attitudes towards business.…”
Section: Literature Reviewmentioning
confidence: 92%
“…Björklund et al, 2010;Malik & Björkqvist, 2019;Meriläinen et al, 2016;Oksanen et al, 2022;Pörhölä et al, 2020) and Greece (e.g. Giovaziolas & Malikiosi-Loizos, 2016;Kokkinos et al, 2016;Spanou et al, 2020) have shown a strong interest in the topic. Other countries where bullying in higher education has been the subject of research include China (Su et al, 2022;Zhao et al, 2022), India (Kaur & Kaur, 2023;Sinha & Bondestam, 2022), Pakistan (Ahmed et al, 2022), South Africa (Badenhorst & Botha, 2022), Spain (Yubero et al, 2023), Turkey (Akbulut & Eristi, 2011) and the United Arab Emirates (Al-Damarki et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Αρκετές μελέτες έδειξαν τη θετική συσχέτιση που έχει η λεκτική επιθετικότητα με την εξωτερική ρύθμιση και την ματαίωση και την εμφάνιση του σωματικού και γνωστικού στρες . Υπήρξε μια συσχέτιση μεταξύ της λεκτικής επιθετικότητας των εκπαιδευτών αθλημάτων και του αυταρχικού στυλ διδασκαλίας και του μη δημοκρατικού κλίματος στην τάξη (Hassandra et al, 2007;Bekiari, 2014) Ακόμη, η λεκτική επιθετικότητα εξετάστηκε σε σχέση με τα δίκτυα εκφοβισμού (Bekiari, Pachi, & Hasanagas 2017;Spanou, Bekiari, & Theocharis, 2020;Spanou, Bekiari, & Hasanagas, 2021). Επιπλέον, η λεκτική επιθετικότητα των εκπαιδευτών και η θετική συσχέτιση με το αυταρχικό στυλ διδασκαλίας και τον μακιαβελισμό των φοιτητών στα πανεπιστημιακά δίκτυα φυσικής αγωγής αποκαλύφθηκε από τους Bekiari και Spanou (2018).…”
Section: λεκτική επιθετικότητα και εκπαίδευσηunclassified